2012
DOI: 10.1242/jeb.073643
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupedal gaits in hexapod animals - inter-leg coordination in free-walking adult stick insects

Abstract: SUMMARYThe analysis of inter-leg coordination in insect walking is generally a study of six-legged locomotion. For decades, the stick insect Carausius morosus has been instrumental for unravelling the rules and mechanisms that control leg coordination in hexapeds. We analysed inter-leg coordination in C. morosus that freely walked on straight paths on plane surfaces with different slopes. Consecutive 1.7s sections were assigned inter-leg coordination patterns (which we call gaits) based on footfall patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 48 publications
11
123
0
1
Order By: Relevance
“…It also bears similarities with the changes in the coordinating influences between straight and curve walking (Dürr, 2005). The fact that these influences may not be equally strong between different thoracic segments also matches earlier descriptions of stick insect walking, in which the front legs have been described to act as 'feelers' (Cruse, 1976), and is also in accordance with the finding that temporal coupling between middle legs and hindlegs during walking is much stronger than that of either leg to the front legs (Dürr, 2005;Grabowska et al, 2012). The functional significance of this could be that the front legs may, in addition to their function in locomotion, also be used for exploratory purposes, while the middle legs and hindlegs serve mostly as an entity for locomotion.…”
Section: Targeting Accuracy Changes Between Standing and Moving Targesupporting
confidence: 84%
“…It also bears similarities with the changes in the coordinating influences between straight and curve walking (Dürr, 2005). The fact that these influences may not be equally strong between different thoracic segments also matches earlier descriptions of stick insect walking, in which the front legs have been described to act as 'feelers' (Cruse, 1976), and is also in accordance with the finding that temporal coupling between middle legs and hindlegs during walking is much stronger than that of either leg to the front legs (Dürr, 2005;Grabowska et al, 2012). The functional significance of this could be that the front legs may, in addition to their function in locomotion, also be used for exploratory purposes, while the middle legs and hindlegs serve mostly as an entity for locomotion.…”
Section: Targeting Accuracy Changes Between Standing and Moving Targesupporting
confidence: 84%
“…Previous studies reported stump oscillations or muscle activity in otherwise intact walking insects (Hughes, 1957;Delcomyn, 1988Delcomyn, , 1991avon Buddenbrock, 1921;Wendler, 1966;Graham, 1977;Bässler et al, 1987;Grabowska et al, 2012). These studies report multiple stump oscillations during single steps in intact legs but were often only qualitative and focused on effects of amputations on the remaining intact legs.…”
Section: New Insights and Open Questionsmentioning
confidence: 99%
“…In other challenging walking situations, such as forward walks on an inclined surface, a particular modification of common stepping patterns is revealed. In stick insects, the front legs become uncoupled from normal locomotion, showing multiple stepping, while the middle and hind leg coordination remains regular (Grabowska et al, 2012).…”
Section: Specializations Of Leg Pairsmentioning
confidence: 99%
“…It should be noted that this kind of classification represents idealized forms of coordination patterns, but walking insects produce also intermediate versions to avoid jerky movements (Grabowska et al, 2012). The different gait patterns described show a transition into each other, forming a continuum (Schilling et al, 2013;Wilson, 1966).…”
Section: Introductionmentioning
confidence: 96%